2021
DOI: 10.3390/dj9110125
|View full text |Cite
|
Sign up to set email alerts
|

Use of Computer Simulation in Dental Training with Special Reference to Simodont

Abstract: Simulation-based dental education has been increasingly implemented in dental training. Virtual reality simulators are being explored as an adjunct to dental education. Simulation-based dental education could serve as a powerful aid to preclinical instruction. This article provides an overview of how dental simulators can be used in dental instruction and manual dexterity training, utilizing the Simodont dental trainer as a reference. The Simodont dental trainer provides a platform for students to hone their m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 16 publications
(30 reference statements)
1
11
0
Order By: Relevance
“…Despite the encouraging feedback of the participants in this study with regards to the positive effect of the HVRS on their fine motor skills and confidence in performing the pulpotomy procedure, the majority of the students felt that hardness, texture and tactile sensations offered by the HVRS device were not realistic. These results are in agreement with other studies where less than third of the students felt the hardness, texture, and tactile sensations of the HVRS devices to be realistic [21], with students also finding the experience of drilling in plastic teeth to be more 'real' than haptic drilling [1,29].…”
Section: Discussionsupporting
confidence: 91%
“…Despite the encouraging feedback of the participants in this study with regards to the positive effect of the HVRS on their fine motor skills and confidence in performing the pulpotomy procedure, the majority of the students felt that hardness, texture and tactile sensations offered by the HVRS device were not realistic. These results are in agreement with other studies where less than third of the students felt the hardness, texture, and tactile sensations of the HVRS devices to be realistic [21], with students also finding the experience of drilling in plastic teeth to be more 'real' than haptic drilling [1,29].…”
Section: Discussionsupporting
confidence: 91%
“…The notion that students perceive some aspects of the conventional training simulators as more realistic is not uncommon; Leung et al, 2021, found that 79% of dental students agreed that traditional simulations ‘felt more realistic’ compared to the VR haptic-based simulator Simodont. Nevertheless, generally there is a positive regard for haptics by dental students, which suggests this technology has a firm place alongside traditional simulators [ 19 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is where simulators that are coupled with virtual reality (VR) and haptic technologies come in, integrating an immersive virtual 3D experience and touch feedback into the simulation [ 18 , 19 ]. Haptic technology creates the perception of touch by administering mechanical pressure/forces to the users on an interface, stimulating the tactile receptors in the skin which in turn triggers motor function.…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] These novel technologies, such as virtual and haptic dental simulators using artificial intelligence assessment systems, are remarkably improving dental undergraduates' understanding of the composites of their expertise as well as the precision and granularity of their bimanual technical skill classification. [7][8][9] However, when young dental students first move into a simulation laboratory and start using handpieces and phantom heads, basic preclinical dental skills, such as cavity preparation and polishing, often feel difficult to learn. This is due to the cognitively demanding all-new and stressful environments where the undergraduates must learn how to triage and act.…”
Section: Introductionmentioning
confidence: 99%